A novel lytic phage infecting MDR Salmonella enterica and its application as effective food biocontrol - Jaglan, Anu Bala; Verma, Ravikant; Vashisth, Medhavi; Virmani, Nitin; Bera, B. C.; Vaid, R. K.; Anand, Taruna (Frontiers in microbiology, 2024)
Salmonella enterica is a foodborne pathogen associated with both typhoid and non-typhoid illness in humans and animals. This problem is further exacerbated by the emergence of antibiotic-resistant strains of Salmonella enterica . Therefore, to meet public health and safety, there is a need for an alternative strategy to tackle antibiotic-resistant bacteria. Bacteriophages or (bacterial viruses), due to their specificity, self-dosing, and antibiofilm activity, serve as a better approach to fighting against drug-resistant bacteria. In the current study, a broad-host range lytic phage phiSalP219 was isolated against multidrug-resistant Salmonella enterica serotypes Paratyphi from a pond water sample. Salmonella phage phiSalP219 was able to lyse 28/30 tested strains of Salmonella enterica . Salmonella phage phiSalP219 exhibits activity in acidic environments (pH3) and high temperatures (70°C). Electron microscopy and genome analysis revealed that phage phiSalP219 is a member of class Caudoviricetes . The genome of Salmonella phage phiSalP219 is 146Kb in size with 44.5% GC content. A total of 250 Coding Sequence (CDS) and 25 tRNAs were predicted in its genome. Predicted open reading frames (ORFs) were divided into five groups based on their annotation results: (1) nucleotide metabolism, (2) DNA replication and transcription, (3) structural proteins, (4) lysis protein, and (5) other proteins. The absence of lysogeny-related genes in their genome indicates that Salmonella phage phiSalP219 is lytic in nature. Phage phiSalP219 was also found to be microbiologically safe (due to the absence of toxin or virulence-related genes) in the control of Salmonella enterica serovar Typhimurium infections in the ready-to-eat meat and also able to eradicate biofilm formed by the same bacterium on the borosilicate glass surface.